MEDIA TECHNOLOGIES IN INFORMATICS CLASSES IN GENERAL EDUCATION SCHOOLS - Umidjon Abdukarimovich Nuraliyev (Journal Park Publishing, 2023)
This article discusses the use of media technologies in informatics classes in general education schools. The article also analyzes ideas about interactive table, media technologies and visual education. Conclusions are given about the advantages of using interactive table in 5th grade of schools, as well as about the existing disadvantages, aspects that are important to pay attention to when organizing lessons.
Keywords: media technologies, interactive table, visual learning, demonstration principle.